Preparação e caracterização térmica e estrutural de cerâmicas UO2 - Gd2O3 - Barco, Reginaldo (2002)
Ceramic pellets of UO2-X%wtGd2O3 were prepared by sintering urania and gadolinia powders, in H2-N2 atmosphere, for 4 hours at a temperature of 1,700°C, compacted with different pressures, in the compositions X = 0, 3, 7 and 10. The samples were characterized by X-ray diffractometry and thermal diffusivity measurements. The X-ray spectra were analyzed by two methods: individual fit of the peaks and Rietveld's refinement (Fullprof Program). In both methods, the analysis revealed that sintering in the time and temperature above produces the diffusion of gadolinia in urania, resulting in a mixed oxide where a "pure" urania phase (UO2) and a solid solution phase (U1-y,Gdy)O2 coexist, with the structure of fluorite. The lattice parameter of the urania phase obtained from the diffractometry analysis showed or to remain constant either to decrease with the concentration X, depending on the analysis method adopted. By the other side, the lattice parameter of the solid solution phase decreases with increasing X. The thermal diffusivity, α(T), was measured by using the "laser-flash" method in the temperature range of 100°C < T < 1,200°C. The mathematical routine applied in the determination of diffusivity is based on the R. Cowan model and was run in situ by a microprocessor that integrates the diffusivimeter set. Making use of an empirical equation for the specific heat Cp(T), the thermal conductivity, k(T) = α(T) Cp(T) ρ, was calculated. It can be observed that the conductivity for every composition decreases with temperature according to the equation k=1/(A+BT), where A and B reveal to depend on the initial gadolinia concentration and on the total porosity of the pellet P. For a given temperature the thermal conductivity decreases with the increasing of X or P. At more elevated temperatures it is possible to express the thermal resistance by R = 1/k = A + BT - CT2 due to a deviation of linearity in the function R(T), more evidently observed for higher concentrations